Persepsi Negatif Mahasiswa Jurusan Pendidikan Mengenai Profesi Menjadi Guru - Hafidah, Delisa; Amelia, Devina; N, Agni Nazwa; Fithriya, Raden Ayu Intan; Aufa, Mazaya Faudya Nur; Mardiant, Ardhan; Rozak, Rama Wijaya Abdul (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The key to educational success lies in the role of the teacher. The presence of teachers who have good qualifications and professionalism is crucial to achieve this goal. One of the important steps to becoming a professional teacher is to complete a Bachelor of Education program. But not all students who take education study programs have an interest in becoming teachers. This is due to a bad perception of the teaching profession. This study aims to determine the emergence of negative perceptions of students majoring in education about the teaching profession. The type of research used in this study is descriptive qualitative, data collection techniques through interviews with seven students selected using purposive sampling, and meeting research criteria. The results showed that the selection of accounting education majors was influenced by various factors, including fear of not passing the selection to enter the dream study program, as well as extrinsic motivation, namely from teachers. The role of teachers in influencing students' choice of majors and careers is crucial. However, negative stigma against the teaching profession, especially related to low salaries, may make some participants hesitant to choose the teaching profession. However, some participants still open the opportunity to become a teacher as a last resort, especially if there is no other option to go to